Self-Efficacy: A Brief Literature Review - Lianto, Lianto (JURNAL MANAJEMEN MOTIVASI, 2019)
Today there is a huge need for a scientific literature review especially for researchers who are preparing research proposals. Scientific journals are mostly filled with research results that are proof of the theory. There are not many articles that contain a literature review on an actual issue. This essay aims to present a concise literature review of self-efficacy. The discussion focused on exploring the basic theories, definitions, dimensions, sources, roles, and antecedents and consequences of self-efficacy. This paper is expected to contribute especially to researchers who are preparing research proposals on this issue.